Bose-einstein correlations in pp, pPb, and PbPb collisions at √sN N = 0.9–7 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (American Physical Society, 2018)
Quantum-statistical (Bose-Einstein) two-particle correlations are measured in pp collisions at √s = 0.9, 2.76, and 7 TeV, as well as in pPb and peripheral PbPb collisions at nucleon-nucleon center-of-mass energies of 5.02 and 2.76 TeV, respectively, using the CMS detector at the Large Hadron Collider. Separate analyses are performed for same-sign unidentified charged particles as well as for same-sign pions and kaons identified via their energy loss in the silicon tracker. The characteristics of the one-, two-, and three-dimensional correlation functions are studied as functions of the pair average transverse momentum (kT) and the charged-particle multiplicity in the event. For all systems, the extracted correlation radii steadily increase with the event multiplicity, and decrease with increasing kT. The radii are in the range 1–5 fm, the largest values corresponding to very high multiplicity pPb interactions and to peripheral PbPb collisions with multiplicities similar to those seen in pPb data. It is also observed that the dependencies of the radii on multiplicity and kT largely factorize. At the same multiplicity, the radii are relatively independent of the colliding system and center-of-mass energy.